2016
DOI: 10.1007/s10064-016-0978-z
|View full text |Cite
|
Sign up to set email alerts
|

Shear characteristics of calcareous gravelly soil

Abstract: Because of its angularity, crushability, and high void ratio, calcareous gravelly soil has peculiar geotechnical properties. A series of large-scale direct laboratory shear tests was conducted on calcareous gravelly soil taken from coral reefs in the South China Sea. This study aimed to investigate the shear characteristics of calcareous gravelly soil under conditions of varying gradation, water content, density, and mineral composition. The experimental results revealed the extremely different mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(6 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Calcareous sands can be widely observed in tropical marine environment. The intrinsic properties distinguish calcareous sands from other terrigenous sediments both physically and mechanically, in terms of particle angularity, high crushability, and weakly cemented soil structure (Wang et al 2017). As stated by Coop and Atkinson (1993), calcareous sands tend to have very loose fabric, due to particle interlocking effect and extremely high intra-granular void ratios.…”
Section: Introductionmentioning
confidence: 96%
“…Calcareous sands can be widely observed in tropical marine environment. The intrinsic properties distinguish calcareous sands from other terrigenous sediments both physically and mechanically, in terms of particle angularity, high crushability, and weakly cemented soil structure (Wang et al 2017). As stated by Coop and Atkinson (1993), calcareous sands tend to have very loose fabric, due to particle interlocking effect and extremely high intra-granular void ratios.…”
Section: Introductionmentioning
confidence: 96%
“…The soil at the site was classified as sandy gravels, and so the shear-strength parameter values appear to be on the high side, although they are within the range suggested by Duncan and Christopher (2004) and the friction angle range of 40° to 50° for coarse granular material suggested by Terzaghi et al (1996). Wang et al (2017) performed laboratory investigations on gravelly calcareous soil that were found to exhibit a high cohesion and a larger friction angle than other granular materials. In the present case, the XRD results for the debris material reveal that calcium carbonate and clay minerals are predominant.…”
Section: Stability Analysis Of the Slopementioning
confidence: 99%
“…12 XRD patterns for sand fines of debris material 2.6.2 Effect of gravel content on the angle of internal friction, ϕ In the field, gravel content substantially varies over a wide range, which in turn markedly influences the friction angle, ϕ. Dupla et al (2007) performed triaxial tests on soil-rock mixtures and concluded that the volumetric fractionof gravel is the main cause that affects the shear-strength parameters and elastic properties. Studies have been conducted in the past to establish a correlation between ϕ and gravel content(Irfan and Tang 1993;Lindquist 1994; Modley 1999;Iannacchione and Vallejo 2000;Xu et al 2011;Wang et al 2017;Wang et al 2020). This is helpful for obtaining the field value of ϕ based on the gravel content at a particular location.…”
mentioning
confidence: 99%
“…Coop et al [19] investigated the particle breakage degree of coral sand under different shear strains through a ring shear test and discovered that coral sand no longer breaks after reaching a certain shear strain; the initial gradation and normal stress of the sample are the main factors that determine the final gradation. Wang et al [20] conducted a direct shear test on calcareous sand in the South China Sea and found that the cohesion of calcareous sand is much higher than that of quartz sand and increases considerably with the average particle size. Rezvani et al [21] compared the triaxial shear behaviors of two kinds of coral sand with different particle sizes under the same conditions and found significant differences in their stress-strain curves.…”
Section: Introductionmentioning
confidence: 99%